Cobalt Electrocatalyst on Fluorine Doped Carbon Cloth – a Robust and Partially Regenerable Anode for Water Oxidation. Issue 18 (8th August 2022) - Das, Biswanath; Toledo‐Carrillo, Esteban Alejandro; Li, Lin; Ye, Fei; Chen, Jianhong; Slabon, Adam; Verho, Oscar; Eriksson, Lars; Göthelid, Mats; Dutta, Joydeep; Åkermark, Björn
Abstract: The low stability of the electrocatalysts at water oxidation (WO) conditions and the use of expensive noble metals have obstructed large‐scale H2 production from water. Herein, we report the electrocatalytic WO activity of a cobalt‐containing, water‐soluble molecular WO electrocatalyst [Co II (mcbp)(OH2 )] (1 ) [mcbp 2− =2, 6‐bis(1‐methyl‐4‐(carboxylate)benzimidazol‐2‐yl)pyridine] in homogeneous conditions (overpotential of 510 mV at pH 7 phosphate buffer) and after anchoring it on pyridine‐modified fluorine‐doped carbon cloth (PFCC). The formation of cobalt phosphate was identified only after 4 h continuous oxygen evolution in homogeneous conditions. Interestingly, a significant enhancement of the stability and WO activity (current density of 5.4 mA/cm 2 at 1.75 V) was observed for 1 after anchoring onto PFCC, resulting in a turnover (TO) of >3.6×10 3 and average TOF of 0.05 s −1 at 1.55 V (pH 7) over 20 h. A total TO of >21×10 3 over 8 days was calculated. The electrode allowed regeneration of∼ 85 % of the WO activity electrochemically after 36 h of continuous oxygen evolution. Abstract : Water oxidation : Cobalt containing new molecular electrocatalyst on pyridine modified fluorine‐doped carbon cloth as a robust, efficient, and partially regenerable water oxidation anode. A novel design of a hybrid, environmentally benign anode for the use in the electrochemical cells for H2 production from water.